Analysis of SOE Banking Stock Investment as Knowledge for Millenial Generation (Fakultas Ekonomi dan Bisnis, Universitas 17 Agustus 1945 Surabaya, 2023)
The purpose of this study is to analyze the status of state-owned banks in Indonesia and find out which state-owned bank shares are suitable for investment by the younger generation. In addition, it aims to increase knowledge and information about investment and become one of the considerations for the younger generation in choosing a place to invest in state-owned banks. The research method used is descriptive-quantitative, using secondary data as the main material for statistical analysis. The results showed that all state-owned banks were in good condition, the lowest share price was Bank BTN, the highest share price was Bank Mandiri, and the highest profits were Bank Mandiri and Bank BNI. The bank that pays the highest dividend is Bank BRI. The younger generation who are risk averse, want to try investing, and have small capital, are suitable for investing in Bank BTN. If you dare and want big profits, it's better to invest in Bank Mandiri or Bank BNI. But if you want to focus and get big dividends, Bank BRI is the right choice. It cannot be denied that if you want to get big profits, you must be willing to take big risks (High-Risk High Return). Keywords: Investments, stocks, dividends, banks, the millennial generation.